Solve for y 6/(y-2)=-3

Math
6y-2=-3
Multiply each term by y-2 and simplify.
Tap for more steps…
Multiply each term in 6y-2=-3 by y-2.
6y-2⋅(y-2)=-3⋅(y-2)
Cancel the common factor of y-2.
Tap for more steps…
Cancel the common factor.
6y-2⋅(y-2)=-3⋅(y-2)
Rewrite the expression.
6=-3⋅(y-2)
6=-3⋅(y-2)
Simplify -3⋅(y-2).
Tap for more steps…
Apply the distributive property.
6=-3y-3⋅-2
Multiply -3 by -2.
6=-3y+6
6=-3y+6
6=-3y+6
Rewrite the equation as -3y+6=6.
-3y+6=6
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 6 from both sides of the equation.
-3y=6-6
Subtract 6 from 6.
-3y=0
-3y=0
Divide each term by -3 and simplify.
Tap for more steps…
Divide each term in -3y=0 by -3.
-3y-3=0-3
Cancel the common factor of -3.
Tap for more steps…
Cancel the common factor.
-3y-3=0-3
Divide y by 1.
y=0-3
y=0-3
Divide 0 by -3.
y=0
y=0
Solve for y 6/(y-2)=-3

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top